Clostridium fessum sp. nov., isolated from human faeces. Issue 1 (30th January 2021) - Seo, Boram; Jeon, Kyungchan; Baek, Inwoo; Lee, Yung Mi; Baek, Kiwoon; Ko, GwangPyo
Abstract : An obligately anaerobic, Gram-stain-positive and spore-forming strain, SNUG30386 T was isolated from a faecal sample of a healthy Korean subject. The strain formed a round ivory-coloured colony and cells were chained rods with tapered ends, approximately 2.0–2.5×0.6–0.8 μm in size. The taxonomic analysis indicated that strain SNUG30386 T was within the family Lachnospiraceae . According to the 16S rRNA gene sequence similarity, the closest species to strain SNUG30386 T was Clostridium symbiosum (95.6 %), followed by Enterocloster asparagiformis (94.8 %), Enterocloster clostridioformis (94.8 %) and Enterocloster lavalensis (94.6 %). The evolutionary tree based on 16S rRNA gene sequences demonstrated that strain SNUG30386 T had split apart at a unique branch point far from other close relatives. Its DNA G+C content was 48.3 mol% calculated from the whole genome sequence. The major cellular fatty acids were C16 : 0 and C14 : 0 . Compared to those of the closely related species, strain SNUG30386 T showed distinct biochemical activities such as being unable to utilize most of carbon sources except d -glucose and l -arabinose. As a result, based on its unique phylogenetic clade and taxonomic characteristics, we conclude that strain SNUG30386 T represents a novel species within the genus Clostridium, for which the name Clostridium fessum sp. nov. is proposed. The type strain of the novel species is SNUG30386 T (=KCTC 15633 T = JCM 32258 T ).